Mobile liturgy: reflections on the church of England’s daily prayer app - Mann, Joshua (Online - Heidelberg journal of religions on the internet, 2017)
Technologies used to represent texts are not hermeneutically neutral. Since technologies have illocutionary force, we should ask of any text, whether print or digital, In what ways are the associated technologies conveying meaning? In this article, the question will be asked of liturgical texts. For the past few years, the Church of England has published some of its Common Worship liturgical resources, including Daily Prayer and the Common Worship Lectionary, as mobile Android and iOS apps. While the content of the resources is generally the same in its printed and digital forms, a number of interesting differences in how the resources can be used in these respective formats are apparent. Further, it is the contention of this article that these differences have discernable hermeneutical effects on the reader/user experience. After offering a framework for understanding the ways in which technologies influence the interpretation of their texts, this article will describe and interpret the differences between the print and digital versions of Daily Prayer. Finally, implications for users/readers and various other stakeholders in the religious apps space will be offered.